Pengaruh Elektrode Sangkar Persegi Pada Resistans Pentanahan Satu Batang Di Lokasi Sempit - Harnoko Stephanus (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Grounding rod is more practical than grounding plate or grounding strip. Grounding resistance value must be set as small as possible, but it is hard to approach the standard grounding resistance value. There are some methods used to reduce grounding resistance such as: paralleling ground rod, extending ground rod, or enlarging ground rod diameter. This paper explains the influence of square cage electrode (1x1 meter) on single ground rod resistance value. In this research, ground rod’s length and diameter were 1.5 meters and 12 millimeters respectively. Ground rod was planted on the ground while the butt was on land surface. Grounding resistance value of that single ground rod was then compared with grounding resistance value of the combination of single ground rod and the square cage electrode (dimension 1x1 meter). The results show that : (a) 1x1 meter square cage electrode with four edge rod (length 0.5 meters; diameter 12 millimeters) can minimize grounding resistance value of single ground rod (length 1.5 meters, diameter 12 millimeters) by 29 ohms. (b) 1x1 meter square cage electrode with eight edge rod (length 0.5 meters; diameter 12 millimeters) can minimize grounding resistance value of single ground rod (length 1.5 meters, diameter 12 millimeters) by 32 ohms.